IDENTIFIKASI DAN PERANCANGAN PENGENDALI PID MENGGUNAKAN PENDUGA ARX TERHADAP SISTEM PEMANAS UDARA DENGAN KRITERIA ISE, IAE, ITSE DAN ITAE - Khuriati RS, Ainie (BERKALA FISIKA, 2012)
In this paper ARX estimation methodology used to design a PID controller  for  temperature control of the air heater. The step input applied  on heating systems and logging the data   to MATLAB via a data acquisition system. The data obtained is used to identify the model ofthe process in the form of ARX estimator. PID parameters obtained by minimising the  standard errors integral(IAE, ISE, ITSE and ITAE).Keywords: PID controller, Tuning, ARX Identication, Error Integral ,and air heater